Mathematical Concepts and Cultural Values at Abui Community Culture: Ethnomathematics Study in Traditional Villages, Alor Regency, Indonesia - Auw, Ester M.N. Elly; Son, Aloisius Loka; Laja, Yosepha Patricia W. (Indonesian Educational Research Journal, 2024)
This study aims to explore mathematical concepts and cultural values in the Abui community, in the village of Takpala, Alor Regency, Indonesia. The research method used is qualitative research with an ethnographic approach. The research subjects are three informants and the research objects are the Fala foka house, Lopo, Moko, and the Lego-lego dance. The instruments used in this research are observation, interviews, and documentation. The research findings obtained include: 1) mathematical concepts found in Fala foka, Lopo, Moko, and Lego-lego dance in the traditional village of Takpala are plane figures such as squares, circles, rectangles, rhombuses, and triangles, as well as spatial figures such as square pyramids, cylinders and pointed cones, and concepts of lines and sets; 2) cultural values found in the roof of Fala foka include supplication, the attic symbolizes unity, the pillars symbolize the four cardinal directions, Lopo symbolizes purity, Moko symbolizes the identity of the Alor community, and the Lego-lego dance symbolizes unity. It is recommended for teachers to apply the results of this research in the learning process, and for further researchers to use the results of this research in designing mathematics learning based on ethnomathematics.